Perang Enam Hari Menandai Kemunduran Arab; Kritik Sosio-Politik Nizzar Dalam Hawamisy ‘Ala Daftar Al-Naksah - Hasibuan, Khairani; Kamil, Sukron; Matondang, Arnan Pahmi (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
This research purpose to reveal the social facts of the six-day war that became the genetic birth of the poem Hawāmisy ‘ala Daftar al-Naksah and the author's worldview towards the defeat of the Arab nation in the war. The method used in this study uses a qualitative method with the approach of Lucien Goldmann's genetic structuralism theory. This theory emphasizes the relationship between literary works and their social environment through the author's worldview. The findings in this study are criticisms directed at the Arab nation because of their intellectual, economic, cultural, and political backwardness. The socio-political criticisms include; the romanticism of the Arab nation, the spontaneity and. expressiveness of Arab society, backward culture, the lack of a democratic system and guarantee of human rights.